Implementation of a Composting Program in Increasing Environmental Responsibility in Primary School Students - Rian Priambodo, Adityo; Ardy Wiyani, Novan (International Proceedings of Nusantara Raya, 2024)
This study explores the implementation of composting program at elementary school as an effort to increase environmental responsibility among students. However, based on the observation, the composting program can encourage the participation of students to be active in protecting the school environment. The purpose of this study is to examine the effectiveness of the composting program in building a learning community that cares about the environment at elementary school. The type of research is descriptive qualitative, data collection without settings by researchers, by conducting observations, interviews and documentation in data collection. The aspects studied were the implementation and impact of the composting program. In the implementation, students better understand the process of recycling and decomposing organics. In terms of impact, students showed increased participation in keeping the environment clean, both at school and at home. The barriers are in the implementation of the composting program, measuring the level of success, and the availability of organic materials. The conclusion of this study is that the implementation of the composting program in elementary school is going well. Student implementation can run well according to the correct recycling process. The impact of students shows an increase in responsibility for the environment.